Non-noble metal heterogeneous catalyst as well as preparation method and application thereof
Through the indium zinc bimetal oxide catalyst doped with aluminum, the existing catalysts are insufficient, complex and costly, and efficient catalysis of CO2 conversion into high value-added chemicals is achieved, and the process flow is simplified.
Patent Information
- Application Number
- CN202411662683.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-14
AI Technical Summary
The existing homogeneous catalysts have insufficient catalytic activity in the reaction of CO2, H2 and dimethylamine, and the preparation process is complicated, the use of precious metals is high, and it is difficult to separate, which affects the economicality and efficiency of production.
A non-precious metal heterophasic catalyst, including indium zinc bimetal oxide and doped aluminum, was developed, prepared by co-precipitation, simplifying the process and reducing costs.
The catalyst exhibits excellent catalytic activity and stability in the reaction of CO2, H2 and dimethylamine, which improves the yield and selectivity of N,N-dimethylformamide, and is simple to operate and low cost.
Smart Images

Figure CN119425660A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst technology, and in particular to a non-precious metal multiphase catalyst and a preparation method and application thereof. Background Art
[0002] As one of the main components of greenhouse gases, excessive CO2 emissions have had a serious impact on the global climate and environment. Therefore, it is crucial to reduce the atmospheric CO2 concentration and achieve CO2 emission reduction. N,N-dimethylformamide (DMF) is an excellent solvent and an important chemical intermediate, with an annual output of millions of tons. Using catalytic technology to catalyze the conversion of CO2 into high-value-added chemicals N,N-dimethylformamide can not only achieve CO2 emission reduction, but also has important significance for the sustainable development of society.
[0003] At present, most catalysts used for the reaction of CO2, H2 and dimethylamine to prepare DMF are homogeneous catalysts. The advantage of the catalyst being in phase with the reaction system is that the formation and conversion of reaction intermediates can be more effectively promoted through the interaction between the ligand and the metal and the modulation of the metal valence state. This contact mode allows the active sites of the catalyst to be fully utilized and significantly improves the catalytic performance. However, the preparation process of homogeneous catalysts is usually complicated, and most of them use precious metals as basic materials, which are expensive. In addition, the stability of the complex of homogeneous catalysts is sometimes not fully guaranteed. In the reaction system, homogeneous catalysts, reactants and products coexist, which makes them difficult to separate from each other. This coexistence property may increase the difficulty of separation and purification in industrial production, thereby affecting the economy and efficiency of the entire production process. Therefore, it is of great practical significance to develop an efficient, mild, and heterogeneous non-precious metal catalytic system.
[0004] Indium (In)-based catalysts are widely used as catalytic synthesis hydrogenation catalysts due to their excellent CO2 hydrogenation activity. In recent years, researchers have developed In-based InZnO x The catalyst was prepared and confirmed to have excellent ability to prepare N-methylformamide by hydrogenation of CO2, but the catalytic activity of the catalyst was insufficient when dimethylamine was used as a substrate to prepare N,N-dimethylformamide. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a non-precious metal heterogeneous catalyst and its preparation method and application. The non-precious metal heterogeneous catalyst provided by the present invention exhibits excellent catalytic activity in the reaction of carbon dioxide, hydrogen and dimethylamine to produce N,N-dimethylformamide.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides a non-noble metal multiphase catalyst, comprising an indium zinc bimetallic oxide and an aluminum element doped in the indium zinc bimetallic oxide.
[0008] Preferably, the molar amount of indium in the non-precious metal heterogeneous catalyst is 30% to 60% of the total molar amount of indium and zinc, and the molar amount of aluminum is 2.5% to 10% of the total molar amount of indium, zinc and aluminum.
[0009] Preferably, the molar amount of indium element in the non-precious metal heterogeneous catalyst is 45% of the total molar amount of indium element and zinc element.
[0010] The present invention provides a method for preparing the non-precious metal heterogeneous catalyst described in the above technical solution, comprising the following steps:
[0011] Mixing indium salt, zinc salt, aluminum salt and water to obtain a metal salt mixed solution;
[0012] The metal salt mixed solution and the soluble carbonate are subjected to a coprecipitation reaction to obtain a precipitate;
[0013] The precipitate is calcined to obtain the non-precious metal heterogeneous catalyst.
[0014] Preferably, the initial pH value of the coprecipitation reaction is 6-8.
[0015] Preferably, the coprecipitation reaction comprises sequentially performing heating treatment and room temperature aging, and the temperature of the heating treatment is 60-80°C.
[0016] Preferably, the calcination temperature is 450-550° C., the holding time is 2-5 hours, and the calcination is carried out in an air atmosphere.
[0017] The present invention provides the use of the non-precious metal heterogeneous catalyst described in the above technical solution or the non-precious metal heterogeneous catalyst prepared by the preparation method described in the above technical solution in the reaction of carbon dioxide, hydrogen and dimethylamine to prepare N,N-dimethylformamide.
[0018] Preferably, the reaction is carried out in a batch reactor, the charging pressure of the reaction is ≥3 MPa, the temperature is 230° C., and the volume ratio of hydrogen to carbon dioxide is 1 / 1.
[0019] Preferably, the reaction is carried out in a slurry bed reactor, the reaction temperature is 200-240°C, the reaction pressure is 7.0 MPa, the volume ratio of carbon dioxide to hydrogen is 3 / 1-1 / 3, and the GHSV is 500-2000 mL (CO2+H2) / (g cat ·h), the flow rate of dimethylamine solution is 3.75~22.5mL / (g cath), the mass fraction of the dimethylamine solution is 30wt%.
[0020] The present invention provides a non-precious metal multiphase catalyst, comprising an indium zinc bimetallic oxide and an aluminum element doped in the indium zinc bimetallic oxide. The present invention dopes the metal element aluminum (Al) into the indium zinc bimetallic oxide (InZnO x In the catalyst), the doping of Al can reduce the catalyst particle size and thus increase the specific surface area of the catalyst, while increasing the catalyst stability and inhibiting the deep reduction of In in the catalyst; and the doping of Al can increase the oxygen vacancy concentration in the catalyst, thereby enhancing the adsorption capacity of carbon dioxide (CO2) on the catalyst surface; in addition, the addition of Al can increase the total acid content and acid strength of the catalyst, enhance the adsorption capacity of the catalyst for dimethylamine, and further improve the reaction activity. The non-precious metal heterogeneous catalyst (denoted as InZnAlO) provided by the present invention x The catalyst exhibits excellent catalytic activity and catalytic stability in the reaction of carbon dioxide, hydrogen and dimethylamine to produce N,N-dimethylformamide.
[0021] The results of the embodiment show that with InZnO x Compared with the catalyst, the non-precious metal heterogeneous catalyst (InZnAlO x Catalyst) is used in the reaction of carbon dioxide, hydrogen and dimethylamine to produce N,N-dimethylformamide. The yield of N,N-dimethylformamide is higher and the catalytic activity is stronger. If the batch method is used, at 230℃, charging pressure 6MPa, V(H2) / V(CO2)=1 / 1, and the reaction conditions of 12h, InZnAlO x The yield of N,N-dimethylformamide prepared by the catalyst was 40.7%, and the selectivity of N,N-dimethylformamide reached 98%. x The yield of N,N-dimethylformamide synthesized by the catalyst was only 33%; and at 230°C, InZnAlO x The catalyst has excellent stability, and the catalyst activity did not weaken in 6 cycles of testing. The continuous flow method was used, the reaction temperature was 230°C, the reaction pressure was 7MPa, the CO2 / H2 / dimethylamine molar ratio was 20 / 20 / 1, and GHSV = 500mL (CO2 + H2) / (g cat ·h), dimethylamine methanol solution (30wt%) flow rate is 7.5mL / (g cat h) The optimal DMF yield was 20.9%; the 100h stability test proved that under the flow system, continuous raw material replenishment and product discharge can ensure the smooth and normal reaction and good catalyst stability.
[0022] The present invention provides a method for preparing the non-precious metal multiphase catalyst described in the above technical solution, which can be prepared by a traditional co-precipitation method without the need for anhydrous and oxygen-free conditions, and has simple operation and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 InZnAlO prepared in this example x Catalyst, InZnAlO x (5%) before and after reaction, InZnO prepared in Comparative Example 1 x PXRD characterization results of catalyst and Al2O3, and standard XRD cards of ZnO and In2O3;
[0024] Figure 2 This is the enlarged image of PXRD characterization of different catalysts. Figure 2 (a) is InZnAlO x and InZnO x (a) PXRD characterization magnified image, and standard XRD card of In2O3, (b) InZnAlO x and InZnO x The PXRD characterization magnified image and the standard XRD card of ZnO;
[0025] Figure 3 InZnO x 、InZnAlO x Nitrogen adsorption-desorption isotherms of a series of catalysts;
[0026] Figure 4 InZnO x TEM characterization (a), HRTEM characterization (b) and particle size distribution (c) of (45%);
[0027] Figure 5 InZnAlO x TEM characterization (a), HRTEM characterization (b) and particle size distribution (c) of (5%);
[0028] Figure 6 InZnO x (45%) EDX elemental distribution map of the catalyst;
[0029] Figure 7 InZnAlO x (5%) EDX elemental distribution map of the catalyst;
[0030] Figure 8 InZnO is a catalyst for the reaction of CO2, H2 and dimethylamine to produce DMF. xTEM characterization (a), HRTEM characterization (b) and particle size distribution (c) of (45%);
[0031] Fig. 9 InZnAlO is a catalyst for the reaction of CO2, H2 and dimethylamine to produce DMF. x TEM characterization (a), HRTEM characterization (b) and particle size distribution (c) of (5%);
[0032] Fig.10 After the reaction, InZnAlO x (5%) EDX elemental distribution map of the catalyst;
[0033] Fig.11 InZnAlO x Catalyst 27 Al solid NMR characterization;
[0034] Fig.12 For Al2O3, InAlO x (5%) and ZnAlO x (5%) 27 Al solid NMR characterization;
[0035] Fig.13 InZnAlO with different In / Zn molar ratios prepared in Examples 1, 5 and 6 x Comparison of the catalytic performance of CO2, H2 and dimethylamine in the synthesis of DMF;
[0036] Fig.14 InZnAlO with different Al doping amounts x Comparison of the performance of catalysts for the reaction of CO2, H2 and dimethylamine to produce DMF;
[0037] Fig.15 InZnAlO x (5%) Screening of substrates for the reaction of CO2, H2 and dimethylamine to produce DMF;
[0038] Fig.16 InZnAlO x (5%) The evaluation results of the catalytic performance of the catalyst in the synthesis of DMF from CO2, H2 and dimethylamine at different feed gas CO2 / H2 molar ratios;
[0039] Fig.17 InZnAlO x (5%) The evaluation results of the catalytic performance of the catalyst for the synthesis of DMF from CO2, H2 and dimethylamine at different reaction temperatures (200-250°C);
[0040] Fig.18 InZnAlO x(5%) The evaluation results of the catalytic performance of the catalyst in the synthesis of DMF from CO2, H2 and dimethylamine at different reaction residence times;
[0041] Fig.19 InZnAlO x (5%) The H NMR spectrum of the liquid product of the catalyst after 14 hours of reaction;
[0042] Fig. 20 InZnAlO x (5%) The evaluation results of the catalytic performance of the catalyst in the synthesis of DMF from CO2, H2 and dimethylamine at different initial pressures;
[0043] Fig.21 InZnAlO x (5%) Catalyst dosage test for the synthesis of DMF from CO2, H2 and dimethylamine;
[0044] Fig. 22 InZnAlO x (5%) The stability test results of the catalyst catalyzing the synthesis of DMF from CO2, H2 and dimethylamine;
[0045] Fig.23 InZnAlO x (5%) The H NMR spectrum of the liquid product after the catalyst reacted at 200°C;
[0046] Fig.24 It is the gas chromatogram of the gas product after the InZnAlOx (5%) catalyst reacts at 230°C;
[0047] Fig.25 InZnAlO x (5%) Gas phase spectrum of liquid product after the catalyst reacted at 230°C;
[0048] Fig.26 InZnAlO x (5%) Enlarged view of the gas phase spectrum of the liquid product after the catalyst reacted at 230°C;
[0049] Fig. 27 InZnAlO at different speeds x (5%) Catalytic activity diagram of the catalyst;
[0050] Fig.28 InZnAlO at different temperatures x (5%) Catalytic activity diagram of the catalyst;
[0051] Fig.29 InZnAlO under different gas ratios x (5%) Catalytic activity diagram of the catalyst;
[0052] Fig.30 InZnAlO at different space velocities x (5%) Catalytic activity diagram of the catalyst;
[0053] Fig.31 InZnAlO with different liquid and gas raw material ratios x (5%) Catalytic activity diagram of the catalyst;
[0054] Fig.32 InZnAlO x (5%) Catalyst stability evaluation results. DETAILED DESCRIPTION
[0055] The present invention provides a non-precious metal multiphase catalyst, comprising an indium zinc bimetallic oxide and an aluminum element doped in the indium zinc bimetallic oxide. In the present invention, a portion of the aluminum element is dispersed in the indium zinc bimetallic oxide (InZnO x ) in the lattice, a portion of which is dispersed in an amorphous state on the surface of the indium zinc bimetallic oxide.
[0056] In the present invention, the molar amount of indium element in the non-precious metal multiphase catalyst is preferably 30% to 60% of the total molar amount of indium element and zinc element, more preferably 45%, and the molar amount of aluminum element is preferably 2.5% to 10% of the total molar amount of indium element, zinc element and aluminum element, more preferably 2.5% to 7.5%, and further preferably 5% to 7.5%.
[0057] In the present embodiment, the non-precious metal heterogeneous catalyst is represented by InZnAlO x (w,y), where w represents the percentage of the molar amount of indium in the non-precious metal heterogeneous catalyst to the total molar amount of indium and zinc (n In / (n In +n Zn )), y represents the percentage of the molar amount of aluminum in the non-precious metal heterogeneous catalyst to the total molar amount of indium, zinc and aluminum (n Al / (n In +n Zn +n Al )).
[0058] The present invention provides a method for preparing the non-precious metal heterogeneous catalyst described in the above technical solution, comprising the following steps:
[0059] Mixing indium salt, zinc salt, aluminum salt and water to obtain a metal salt mixed solution;
[0060] The metal salt mixed solution and the soluble carbonate are subjected to a coprecipitation reaction to obtain a precipitate;
[0061] The precipitate is calcined to obtain the non-precious metal heterogeneous catalyst.
[0062] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.
[0063] The present invention mixes indium salt, zinc salt, aluminum salt and water to obtain a metal salt mixed solution. In the present invention, the indium salt, zinc salt and aluminum salt are preferably indium nitrate, zinc nitrate and aluminum nitrate, respectively. In an embodiment of the present invention, the indium nitrate, zinc nitrate and aluminum nitrate are added in the form of In(NO3)3·4H2O, Zn(NO3)2·6H2O and Al(NO3)3·9H2O, respectively; the water is preferably deionized water. In the present invention, the amount of the indium salt, zinc salt and aluminum salt added is preferably based on the molar amount of the indium element being 30% to 60% of the total molar amount of the indium element and the zinc element, and the molar amount of the aluminum element being 2.5% to 10% of the total molar amount of the indium element, the zinc element and the aluminum element. In the present invention, the total molar concentration of the indium salt, the zinc salt and the aluminum salt in the metal salt mixed solution is preferably 0.1 mol / L. In the present invention, the mixing is preferably stirred mixing.
[0064] After obtaining the metal salt mixed solution, the present invention mixes the metal salt mixed solution and a soluble carbonate to carry out a coprecipitation reaction to obtain a precipitate. In the present invention, the soluble carbonate is preferably ammonium carbonate, and the soluble carbonate is preferably added in the form of an aqueous carbonate solution, and the concentration of the soluble carbonate aqueous solution is preferably 0.1-0.5 mol / L, and more preferably 0.3-0.4 mol / L. In the present invention, the initial pH value of the coprecipitation reaction is preferably 6-8, and more preferably 7. Specifically, the soluble carbonate aqueous solution is added dropwise to the metal salt mixed solution until the pH value of the obtained mixed solution is 6-8, and the rate of the addition is preferably 1-5 mL / min, and more preferably 3 mL / min; during the dropwise addition, the temperature of the metal salt mixed solution is preferably 60-80°C, and preferably 70°C, and the metal salt mixed solution is kept stirred, and the stirring rate is preferably 800-1200 rpm, and more preferably 1000 rpm.
[0065] In the present invention, the coprecipitation reaction preferably includes heating treatment and room temperature aging in sequence. In the present invention, the temperature of the heating treatment is preferably 60-80°C, more preferably 70°C; the heating treatment preferably includes stirring treatment and standing treatment in sequence; the stirring rate of the stirring treatment is preferably 600-800rpm, more preferably 700rpm, the stirring treatment time is preferably 1-3h, more preferably 2h; the standing treatment (i.e. stopping stirring) time is preferably 1-3h, more preferably 2h. In the present invention, the room temperature aging time is preferably 0.5-2.5h, more preferably 1.5h.
[0066] After the coprecipitation reaction is completed, the present invention preferably filters, washes and dries the obtained reaction solution in sequence to obtain the precipitate. In the present invention, the drying temperature is preferably 110° C. and the drying time is preferably 8 hours.
[0067] After obtaining the precipitate, the present invention calcines the precipitate to obtain the non-precious metal multiphase catalyst. The present invention preferably grinds the precipitate into powder and transfers it to a muffle furnace for calcination. In the present invention, the calcination temperature is preferably 450-550°C, more preferably 500°C, the insulation time is preferably 2-5h, more preferably 3h, and the heating rate from room temperature to the calcination temperature is preferably 0.5-2°C / min, more preferably 1°C / min; the calcination is preferably carried out in an air atmosphere, and the air atmosphere is preferably flowing air with a flow rate of 100-200mL / min (preferably 150mL / min). After the calcination is completed, it is naturally cooled to room temperature.
[0068] The present invention adopts a coprecipitation method, and the non-precious metal heterogeneous catalyst can be prepared without anhydrous and oxygen-free conditions, and the operation is simple. In the non-precious metal heterogeneous catalyst provided by the present invention, Al is dispersed in an amorphous state in the indium zinc bimetallic oxide (InZnO x ) surface, and is doped in the indium zinc bimetallic oxide lattice. Al doping can reduce the catalyst particle size and thus increase the specific surface area of the catalyst, while increasing the catalyst stability and inhibiting the deep reduction of In in the catalyst; and Al doping can increase the oxygen vacancy concentration in the catalyst, thereby enhancing the adsorption capacity of CO2 on the catalyst surface; in addition, the addition of Al can increase the total acid amount and acid strength of the catalyst, enhance the adsorption capacity of the catalyst for dimethylamine, and further improve the reaction activity. The non-precious metal multiphase catalyst provided by the present invention is used in the reaction of carbon dioxide, hydrogen and dimethylamine to prepare N,N-dimethylformamide, and the yield of N,N-dimethylformamide is high, the catalytic activity is strong, and it has excellent stability; and after the reaction, the catalyst is easy to recover without loss.
[0069] The present invention provides the use of the non-precious metal heterogeneous catalyst described in the above technical solution or the non-precious metal heterogeneous catalyst prepared by the preparation method described in the above technical solution in the reaction of carbon dioxide, hydrogen and dimethylamine to prepare N,N-dimethylformamide.
[0070] In the present invention, the reaction can be carried out in a batch reactor, the charging pressure of the reaction is preferably ≥3MPa, more preferably 6MPa, the temperature is preferably 230°C, the volume ratio of hydrogen to carbon dioxide (V(H2) / V(CO2)) is preferably 1 / 1; the ratio of the mass of the dimethylamine to the mass of the non-precious metal multiphase catalyst is preferably (1.5-3) / 1; the reaction time is preferably 12h. In the present invention, the dimethylamine is preferably from a solution of dimethylamine or a precursor compound of dimethylamine; the solution of dimethylamine is preferably a methanol solution of dimethylamine or a tetrahydrofuran solution of dimethylamine, and the mass fraction of dimethylamine in the solution of dimethylamine is preferably 10% to 40%; the precursor compound of dimethylamine is preferably dimethylamine-N,N-dimethylcarbamate (DIMCARB, which produces dimethylamine after heating and decomposition).
[0071] The intermittent reactor has the characteristics of simple structure, easy operation, wide application range of raw materials, ability to conduct multiple parallel experiments at the same time, high efficiency of catalyst screening per unit time, etc., and shows broad application prospects in the fields of catalysis and organic synthesis. However, since the reaction occurs in a closed environment, it is difficult to observe the reaction phenomenon at each time point, which makes it difficult to study the intermediate state of the reaction in real time. On the other hand, due to the intermittent characteristics of the reactor, as the reaction time is prolonged, the raw materials in the reactor are continuously consumed, the products are continuously increased and may occupy the reaction site, which hinders further progress and limits the improvement of reaction efficiency. The present invention promotes the reaction of carbon dioxide, hydrogen and dimethylamine to produce N, N-dimethylformamide from an intermittent reactor to a mobile phase reactor, which is of great significance to improving reaction efficiency and provides basic data support for industrial application. In the present invention, the reaction can also be carried out in a slurry bed reactor. The present invention has no special requirements for the slurry bed reactor, and a slurry bed reactor well known to those skilled in the art can be used. In the present invention, the reaction temperature is preferably 200-240°C, which may be 200°C, 210°C, 220°C, 230°C or 240°C, more preferably 230°C, the reaction pressure is preferably 7.0 MPa, the volume ratio of carbon dioxide to hydrogen is preferably 3 / 1-1 / 3, which may be 3 / 1, 2 / 1, 1 / 1, 1 / 2 or 1 / 3, more preferably 1 / 1, and the GHSV is preferably 500-2000mL(CO2+H2) / (g cat h), which can be 500, 750, 1000 or 2000 mL (CO2 + H2) / (g cat ·h), more preferably 500mL(CO2+H2) / (g cat In the present invention, the dimethylamine is preferably continuously introduced into the slurry bed reactor in the form of a dimethylamine solution, and the flow rate of the dimethylamine solution is preferably 3.75 to 22.5 mL / (g cath), the mass fraction of the dimethylamine solution is preferably 30wt%; in the embodiment of the present invention, the dimethylamine solution is preferably a dimethylamine methanol solution. In the present invention, the reaction is preferably carried out under stirring, and the stirring rate is preferably 100-400rpm, which can be 100rpm, 250rpm or 400rpm, and more preferably 250rpm.
[0072] In order to further illustrate the present invention, the non-precious metal heterogeneous catalyst provided by the present invention and its preparation method and application are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0073] Comparative Example 1
[0074] Preparation of InZnO by coprecipitation method x Bimetallic oxide catalyst, the steps are as follows:
[0075] First, 2.5166g of In(NO3)3·4H2O and 2.4543g of Zn(NO3)2·6H2O were dissolved in 140mL of deionized water and stirred thoroughly to obtain a mixed solution of metal nitrates. Subsequently, 0.32mol / L of ammonium carbonate solution was added dropwise to the middle of the vortex of the mixed solution of metal nitrates at a rate of 3mL / min using a 50mL syringe at 1000rpm and 70°C until the pH reached 7. Continue to heat and stir at 700rpm and 70°C for 2h, then stop stirring, let stand at 70°C for 2h, and then age at room temperature for 1.5h. Filter and wash with rapid filter paper, and dry at 110°C for 8h. Finally, the solid was ground into powder and transferred to a muffle furnace for calcination. The temperature was raised to 500°C at a heating rate of 1°C / min under flowing air (150mL / min) and maintained for 3h, and then naturally cooled to room temperature to obtain InZnO x Bimetallic oxide catalyst, denoted as InZnO x (45%) (45% means n In / (n In +n Zn )).
[0076] Example 1
[0077] Co-precipitation of Al into InZnO x Preparation of non-precious metal heterogeneous catalysts from bimetallic oxide catalysts (InZnAlO x Catalyst), the steps are as follows:
[0078] First, 2.5166g of In(NO3)3·4H2O, 2.4543g of Zn(NO3)2·6H2O and 0.2961g of Al(NO3)3·9H2O were dissolved in 140mL of deionized water and stirred thoroughly to obtain a metal nitrate mixed solution. Subsequently, 0.32mol / L ammonium carbonate solution was added dropwise to the middle of the vortex of the metal nitrate mixed solution at a rate of 3mL / min using a 50mL syringe at 1000rpm and 70℃ until the pH reached 7. Continue to heat and stir at 700rpm and 70℃ for 2h, then stop stirring, stand at 70℃ for 2h, and then age at room temperature for 1.5h. Filter, wash and dry at 110℃ for 8h using fast filter paper. Finally, the solid was ground into powder and transferred to a muffle furnace for calcination. The temperature was raised to 500 °C at a heating rate of 1 °C / min under flowing air (150 mL / min) and maintained for 3 h. The mixture was then cooled to room temperature to obtain InZnAlO x Catalyst, denoted as InZnAlO x (45%,5%) (45% means n In / (n In +n Zn ), 5% represents n Al / (n In +n Zn +n Al ), the same below) or InZnAlO x (5%), the catalyst appears as light yellow powder.
[0079] Example 2
[0080] The amount of Al(NO3)3·9H2O in Example 1 was changed to 0.1443 g, and the rest was the same as in Example 1 to obtain InZnAlO x Catalyst, denoted as InZnAlO x (45%, 2.5%) or InZnAlO x (2.5%).
[0081] Example 3
[0082] The amount of Al(NO3)3·9H2O in Example 1 was changed to 0.4562 g, and the rest was the same as in Example 1 to obtain InZnAlO x Catalyst, denoted as InZnAlO x (45%, 7.5%) or InZnAlO x (7.5%).
[0083] Example 4
[0084] The amount of Al(NO3)3·9H2O in Example 1 was changed to 0.6252 g, and the rest was the same as in Example 1 to obtain InZnAlO x Catalyst, denoted as InZnAlO x (45%, 10%) or InZnAlO x (10%).
[0085] Example 5
[0086] The amount of In(NO3)3·4H2O in Example 1 was changed to 1.6777 g, and the amount of Zn(NO3)2·6H2O was changed to 3.1236 g. The rest was the same as in Example 1 to obtain InZnAlO x Catalyst, denoted as InZnAlO x (30%,5%).
[0087] Example 6
[0088] The amount of In(NO3)3·4H2O in Example 1 was changed to 3.3555 g, and the amount of Zn(NO3)2·6H2O was changed to 1.7849 g. The rest was the same as in Example 1 to obtain InZnAlO x Catalyst, denoted as InZnAlO x (60%,5%).
[0089] (I) The catalysts prepared in the examples and comparative examples were structurally characterized by XRD, BET, ToF-SIMS, and electron microscopy, as follows:
[0090] (1) XRD characterization
[0091] Figure 1 InZnAlO prepared in this example x Catalyst, InZnO prepared in Comparative Example 1 x PXRD characterization results of catalysts and ZnO, Al2O3, In2O3, Figure 1 InZnO x (45%), InZnAlO x (5%), InZnAlO x (2.5%), InZnAlO x (7.5%), InZnAlO x (10%) corresponds to Example 1, Example 1, Example 2, Example 3, and Example 4, respectively. Figure 1 As shown, in InZnO xIn the catalyst, characteristic peaks of ZnO (JCPDS: 36-1451) and In2O3 (JCPDS: 06-0416) can be seen, indicating that InZnO synthesized by coprecipitation method x The catalyst mainly exists in the form of bimetallic oxides. The diffraction lines of all samples are related to In2O3 (JCPDS: 06-0416) and ZnO (JCPDS: 36-1451). With the addition of Al, no characteristic peaks of Al2O3 were observed, and it is speculated that Al2O3 may be highly dispersed or amorphous. When the Al content exceeds 7.5%, the diffraction lines of In2O3 and ZnO become significantly broadened. As shown in Table 1, the particle size was calculated by XRD and it was found that In2O3 decreased from 21.5nm to 18.0nm, and ZnO decreased from 42.7nm to 11.0nm, indicating that the particle size of In2O3 and ZnO decreased.
[0092] Table 1 XRD calculation of InZnAlO x 、InZnO x In2O3 and ZnO particle size of catalysts in the same series
[0093] Example catalyst <![CDATA[Particle size of In2O3 (nm)]]> ZnO particle size (nm) Comparative Example 1 <![CDATA[InZnO x (45%)]]> 21.5 42.7 Example 2 <![CDATA[InZnAlO x (2.5%)]]> 18.0 11.0 Example 1 <![CDATA[InZnAlO x (5%)]]> 17.6 7.3
[0094] Figure 2 This is the enlarged image of PXRD characterization of different catalysts. Figure 2 (a) is InZnAlO x and InZnO x (a) PXRD characterization magnified image, and standard XRD card of In2O3, (b) InZnAlO x and InZnO x The PXRD characterization magnified image and the standard XRD card of ZnO. Figure 2 As shown, the characteristic peak of In2O3 (JCPDS: 06-0416) was observed to be from 30.595° (InZnO x (45%)) moved to 30.677° (InZnAlO x (2.5%), and with the increase of Al content, the In2O3 diffraction peak further moves to a higher angle, and the characteristic peak of ZnO (JCPDS: 36-1451) moves from 36.253° (InZnO x (45%)) moved to 36.260° (InZnAlO x (2.5%), and with the increase of Al content, the ZnO diffraction peak further moves to a higher angle. It is speculated that Al doping may enter the lattice of In2O3 and ZnO, causing lattice distortion, thus leading to the shift of the diffraction peak.
[0095] InZnAlO after participating in the reaction of CO2, H2 and dimethylamine to produce DMF x (5%) catalyst was subjected to XRD test, and the results were as follows Figure 1 As shown ( Figure 1 InZnAlO x (5%)-used), the reaction conditions of carbon dioxide, hydrogen and dimethylamine to produce N,N-dimethylformamide are: 50mL intermittent high-pressure reactor, 1mL of 30wt% dimethylamine methanol solution, 100mg of catalyst, P=6.0MPa, V(H2) / V(CO2)=1 / 1, T=230℃, t=12h, stirring speed 500rpm. By comparing the XRD of the catalyst before and after the reaction, it was found that InZnAlO x After the reaction of the (5%) catalyst, the characteristic peak of ZnO disappeared, and no ZnO lattice fringes were observed by TEM. It is speculated that the catalyst may have been reconstructed during the reaction (ZnO is highly dispersed).
[0096] (2) Nitrogen adsorption-desorption characterization and ICP-OES characterization
[0097] Figure 3 InZnO x 、InZnAlO x Nitrogen adsorption-desorption isotherms of a series of catalysts. Figure 3 It can be seen from the nitrogen adsorption-desorption isotherm that InZnO x With InZnAlO x The catalyst exhibits a V-shaped isotherm with an H3-type hysteresis loop, indicating that the catalyst may have wedge-shaped pores.
[0098] InZnAlO x 、InZnO x The physical properties of the catalyst elements, specific surface area, etc. are summarized and compared. As shown in Table 2, InZnO x and InZnAlO x The specific surface area, pore volume and average pore diameter of the catalyst are 18.9 to 82.3 m 2 / g, 0.09~0.45cm 3 / g and 9.85~18.98nm. Theoretical n of the synthesized catalyst In / (n In +n Zn ) and n Al / (n In +n Zn +n Al ) ratio and the n measured by ICP-OES In / (n In +n Zn ) and n Al / (nIn +n Zn +n Al ) ratios are very close: the In / Zn content ratios in the catalyst before and after doping are 46% and 47%, respectively, and the tested Al contents are 2.5%, 4.9%, 7.4% and 10.0%, respectively, indicating that there is almost no loss of In, Zn and Al in the process of synthesizing the catalyst by coprecipitation. The addition of Al can make InZnAlO x The specific surface area of the catalyst (53.10~82.30m 2 / g) is much higher than InZnO x (18.90m 2 / g), combined with the catalytic performance of the above-mentioned Al-doped catalyst, it is speculated that with the addition of Al, the specific surface area of the catalyst can be increased and the active sites of the catalyst can be increased. However, with the further increase of Al, some active sites may be covered by Al or the active sites generated by direct contact between In and Zn may be blocked, resulting in a weakened promotion effect.
[0099] Table 2 Catalyst element ratio and catalyst dosage screening
[0100]
[0101] Note: In Table 2, a Theoretical metal ratio of the sample, b The actual metal ratio of the sample determined by ICP-OES, c S BET is the specific surface area of the catalyst, d V tP is the total pore volume, data is taken from 0.99P / P0, e d P,BJH is the pore size calculated from the N2 adsorption isotherm using the BJH model.
[0102] (3) TEM and HRTEM characterization
[0103] Figure 4 and Figure 5 InZnO x (45%) and catalyst InZnAlO x (HR) TEM characterization and particle size distribution of (5%). By analyzing the TEM images of the two, it can be seen that InZnO x (45%) catalysts tend to be more spherical particles, while after doping with Al, the catalyst morphology tends to be irregular particles. x (45%) and InZnAlO xIn2O3(222) and ZnO(002) crystal planes were observed in the (5%) catalyst, but no Al2O3 lattice fringes were observed, suggesting that Al exists mainly in an amorphous form. This is consistent with the result that no Al2O3 characteristic peaks were observed in XRD. x The particle size of (45%) is 18.0±3.8nm, and the doped InZnAlO x The particle size of (5%) is relatively small, 11.9±3.4 nm, indicating that the smaller the particle size, the greater the specific surface area of the catalyst, which is consistent with the decrease in the particle size of In2O3 and ZnO calculated from the XRD data. Figure 6 InZnO x EDX element distribution diagram of the (45%) catalyst, with In, Zn and O elements represented in orange, green and blue, respectively. Figure 7 InZnAlO x The EDX element distribution diagram of the (5%) catalyst shows that In, Zn, O and Al elements are represented by orange, green, blue and red respectively. x The dispersion of Al on the catalyst is good.
[0104] InZnO after participating in the reaction of CO2, H2 and dimethylamine to produce DMF x (45%) and InZnAlO x (5%) catalyst was subjected to TEM test for comparison (reaction conditions were the same as above), and the results were as follows Figure 8 and Fig. 9 As shown, Figure 8 and Fig. 9 InZnO x (45%) and InZnAlO x (HR)TEM characterization and particle size distribution of (5%) catalyst. It can be seen that after the reaction, regardless of InZnO x (45%) and InZnAlO x (5%) catalyst, only In2O3 (222) lattice fringes were observed, and no ZnO lattice fringes were observed. It is speculated that ZnO is an amorphous structure, proving that the catalyst was reconstructed after the reaction. The particle size of the catalyst after the reaction was summarized, and the particle size was slightly enlarged after the reaction (InZnO x (45%) catalyst is 18.0±3.8nm increased to 19±0.2nm)(InZnAlO x (5%) catalyst is 11.9±3.4nm increased to 14.7±0.4nm), the doped InZnAlO x The particle size of (5%) is still smaller than that of the unmodified catalyst. Fig.10 After the reaction, InZnAlO xThe EDX element distribution diagram of the (5%) catalyst, with In, Zn, O and Al elements represented by orange, green, blue and red respectively. It can be seen from the EDX spectrum that the dispersion of Al in the catalyst is still good before and after the reaction, and no Al clusters are observed.
[0105] (4) ToF-SIMS characterization
[0106] ToF-SIMS has the molecular specificity and surface sensitivity to study and reveal the properties of InZnAlO x (5%) The structure of the catalyst. The detector received some typical positive and negative ions.
[0107] As shown in Table 3, Zn x O y The largest fragment is Zn3O2 + and Zn3O4 - , did not reach the upper limit of the analysis setting (x = 6), indicating that Zn x O y Good dispersion in the catalyst. x O y The largest fragment is Al4O5 + and Al6O3 - ,In x O y The largest fragment is In6O6 + and In6O6 - , both reached the upper limit of the analysis setting (x=6), indicating that In x O y With Al x O y There are aggregated forms in the catalyst.
[0108] Table 3 InZnAlO x (5%) Different positive and negative ion fragments in the catalyst
[0109]
[0110] As shown in Table 4, In x Al y O z The ion fragments present are AlInO + 、AlInO2 + and AlInO2 - 、AlInO3 - , indicating the existence of In-O-Al structure. The corresponding AlZnO + 、AlZnO2 + and AlZnO3 - 、AlZnO4- ; ZnInO + 、ZnInO2 + and ZnInO - 、ZnInO2 - This indicates the existence of Zn-O-Al and In-O-Zn structures respectively.
[0111] Table 4 InZnAlO x (5%) Different positive and negative ion fragments in the catalyst
[0112]
[0113] (5) Solid-state NMR
[0114] use 27 Al NMR spectroscopy was used to study the Al content in different aluminum-containing samples. 3+ The local environment of the site. Fig.11 As shown, the signals of these samples contain 60-85 ppm (tetracoordinated Al (Al IV )), 35-50ppm (pentacoordinated Al (Al V )) and 4-15ppm (hexacoordinated Al (Al VI Three signals appear at 11.5-18.0ppm, indicating the presence of three structures of hexacoordinated Al, which are presumably from Al species doped into In2O3; Al species doped into ZnO and InZnO x The Al species are highly dispersed on the surface. For InZnAlO x (5%) Catalyst (InZnAlO x (5%)-used), the peak of the six-coordinate region at 11.5 ppm disappeared after the reaction, indicating that the Al species on the catalyst surface were reconstructed during the reaction.
[0115] To assign the two six-coordinated Al signals, Al2O3, InAlO x (5%), ZnAlO x (5%) 27 Al NMR spectrum test, the results are as follows Fig.12 As shown. In Al2O3, it is found that the six-coordinated Al (8.2ppm) and the four-coordinated Al (67.5ppm) are both single peak signals. x (5%) 27 Al spectrum test found that there were two peaks near the hexacoordinated Al and tetracoordinated Al. x(5%) also found two peaks, but the signal intensity and peak position were obviously different. Therefore, 8.0-11.2ppm was attributed to InZnO x The Al species are highly dispersed on the surface; 14.0ppm is attributed to the Al species doped into the ZnO lattice; 18.0ppm is attributed to the Al species doped into the In2O3 lattice. It is speculated that Al is doped to a certain extent in both the ZnO and In2O3 lattices, but Al is mainly doped into the ZnO lattice, which makes the characteristic signal of the catalyst at 14.0ppm more obvious. In addition, XRD also proves that Al doping causes the characteristic peaks of ZnO and In2O3 to move to higher angles.
[0116] (ii) Catalytic performance (production of DMF by reaction of CO2, H2 and dimethylamine) of the catalysts prepared in the examples and comparative examples was tested using an intermittent high-pressure reactor (i.e., intermittent method)
[0117] (1) InZnAlO with different In / Zn molar ratios x Catalytic performance
[0118] Fig.13 InZnAlO with different In / Zn molar ratios prepared in Examples 1, 5 and 6 x Comparison of the performance of catalytic synthesis of DMF by CO2, H2 and dimethylamine. Fig.13 The horizontal axes 30%, 45%, and 60% correspond to Example 5, Example 1, and Example 6, respectively. Reaction conditions: 50 mL batch autoclave, 100 mg, 6.0 MPa, V(H2) / V(CO2)=1 / 1, T=230°C, t=12 h, 1 mL of 30 wt% dimethylamine methanol solution, 500 rpm. Fig.13 It can be seen that the InZnAlO prepared in Example 5 and Example 6 with different In / Zn molar ratios x It also shows good catalytic effect.
[0119] (2) InZnAlO with different Al doping amounts x Catalytic performance
[0120] like Fig.14 As shown, the present invention optimizes the metal doping amount. As the Al content increases (n In / (n In +n Zn )=0.45), the yield of DMF showed a "volcano-like" change, the reaction performance first improved, and reached the optimal value of 40.7% when Al was 5%. As Al further increased, the catalytic performance decreased to a certain extent, but was higher than that of InZnO xThe results show that the addition of Al can significantly promote the catalytic activity, but the promotion effect gradually weakens with the further increase of the doping amount.
[0121] (3) Substrate screening.
[0122] Dimethylamine has different raw material options. In order to compare the effects of different raw materials and raw material dosages on catalytic activity, substrate tests were performed.
[0123] Fig.15 InZnAlO x (5%) Catalyst catalyzed the reaction of CO2, H2 and dimethylamine to produce DMF. The reaction conditions were: 50 mL intermittent high-pressure reactor, 100 mg catalyst, P = 6.0 MPa, V(H2) / V(CO2) = 1 / 1, T = 230°C, t = 12 h, and stirring speed of 500 rpm.
[0124] like Fig.15 As shown, dimethylamine-N,N-dimethylcarbamate (DIMCARB) is a commonly used dimethylamine raw material. It takes a certain amount of time to decompose before providing dimethylamine, so the DMF yield is lower than that of methanol dimethylamine solution. After adding methanol as a solvent to DIMCARB, the DMF yield is improved to a certain extent. This is because the addition of methanol solvent can effectively disperse dimethylamine, which is beneficial to improving catalytic activity. After comprehensive consideration, a mixed solution of dimethylamine and methanol (the mass fraction of dimethylamine is 30wt%) is selected as the substrate, and the liquid dosage is selected as 1mL.
[0125] (4) Optimization of catalytic conditions
[0126] In order to obtain the optimal catalytic conditions, the InZnAlO catalysts with different CO2 / H2 molar ratios, reaction temperatures, reaction residence times and initial total reaction pressures were tested. x (5%) CO2 catalytic hydrogenation performance of the catalyst.
[0127] Fig.16 InZnAlO x The evaluation results of the catalytic performance of the (5%) catalyst for the synthesis of DMF from CO2, H2 and dimethylamine at different feed gas CO2 / H2 molar ratios. Reaction conditions: 50mL intermittent autoclave, 100mg catalyst, pressure 6.0MPa, V(CO2) / V(H2)=1 / 5, 2 / 4, 1 / 1, 4 / 2 or 5 / 1, T=230℃, t=12h, 1mL of 30wt% dimethylamine methanol solution, 500rpm. Fig.16As shown, the different initial feed CO2 / H2 molar ratios significantly affect the CO2 conversion rate. The DMF yield shows a "volcano-shaped" change. The DMF yield first increases and then decreases with the increase of the CO2 / H2 molar ratio. The chemical equation is CO2+H2+NH(CH3)2→HCON(CH3)2+H2O. When the H2 / CO2 molar ratio is 1 / 1, that is, the stoichiometric ratio is reached, the optimal catalytic performance is achieved.
[0128] Reaction temperature is also one of the factors that affect the catalytic reaction. Fig.17 InZnAlO x The evaluation results of the catalytic performance of the (5%) catalyst for the synthesis of DMF from CO2, H2 and dimethylamine at different reaction temperatures (200-250°C). Reaction conditions: 50mL intermittent autoclave, 100mg catalyst, 6.0MPa, V(H2) / V(CO2)=1 / 1, T=200-250°C, t=12h, 1mL of 30wt% dimethylamine methanol solution, 500rpm. Fig.17 As shown in Figure 2, the DMF yield increases with the increase of reaction temperature from 200 to 230°C and gradually decreases at 230 to 250°C. When the temperature is close to 230°C, the DMF yield reaches a maximum of 40.7% (while the same conditions are used with InZnO x (45%) The yield of synthesized DMF is only 33%). Since the reaction is an exothermic reaction, as the temperature further increases, the chemical equilibrium moves toward the reactants, which is not conducive to the formation of DMF.
[0129] The catalyst performance under different reaction residence times was investigated. Fig.18 InZnAlO x Evaluation results of the catalytic performance of the (5%) catalyst for the synthesis of DMF from CO2, H2 and dimethylamine at different reaction residence times. Reaction conditions: 50mL intermittent high-pressure reactor, 100mg catalyst, 6.0MPa, V(H2) / V(CO2)=1 / 1, T=230℃, t=4-14h, 1mL of 30wt% dimethylamine methanol solution, 500rpm. It was found that the product yield is dependent on the reaction residence time. The DMF yield increases with the extension of the reaction time and reaches the maximum value at 12h; at the same time, as the time further increases, the DMF yield decreases. Fig.19 InZnAlO x(5%) The liquid product NMR hydrogen spectrum of the catalyst after 14 hours of reaction, reaction conditions: 50mL intermittent high-pressure reactor, 100mg, P = 6.0MPa, V (H2) / V (CO2) = 1 / 1, T = 230 ° C, t = 14h, 30wt% dimethylamine methanol solution 1mL, 500rpm. Through liquid NMR testing, it was found that at 14h, a certain amount of trimethylamine appeared, and it was speculated that the conversion of dimethylamine required a long time. However, as the reaction residence time further increases, some DMF will be further reduced by H2 to generate trimethylamine. Therefore, a residence time of 12h was selected for the catalytic reaction.
[0130] Fig. 20 InZnAlO x The evaluation results of the catalytic performance of the (5%) catalyst for the synthesis of DMF from CO2, H2 and dimethylamine at different initial pressures. Reaction conditions: 50mL intermittent high-pressure reactor, 100mg, 3.0-7.0MPa, V(H2) / V(CO2)=1 / 1, T=230℃, t=12h, 1mL of 30wt% dimethylamine methanol solution, 500rpm. Fig. 20 As shown, since the preparation of DMF by hydrogenation of CO2 is a reaction in which the number of gas molecules decreases, the DMF yield increases with the gradual increase of the reaction pressure, and increases dramatically from 26.2% to 40.7% when the charging pressure is 6MPa. Although the catalytic performance can be improved with further increase, the pressure resistance and safety requirements of the equipment are higher. Considering comprehensively, the catalytic performance evaluation was carried out when the system charging pressure was 6MPa.
[0131] In summary, within the range of conditions studied, InZnAlO x The optimal reaction conditions for the (5%) catalyst to be used for CO2 hydrogenation are reaction pressure P ≥ 3MPa, reaction gas ratio V(H2) / V(CO2) = 1 / 1, reaction temperature T of 230°C and reaction residence time t of 12h. Under the optimal reaction conditions, the DMF yield is 43.2%.
[0132] (5) Catalytic stability test
[0133] Under the determined optimal reaction conditions, InZnAlO x (5%) catalyst was used for CO2 hydrogenation reaction and 6 consecutive catalytic stability evaluations were conducted. To ensure the credibility of the data, the catalyst dosage test was first conducted. Fig.21 As shown, the reaction conditions are: Reaction conditions: 50mL intermittent high-pressure reactor, P = 6.0MPa, V (H2) / V (CO2) = 1 / 1, T = 230 ° C, t = 12h, 30wt% dimethylamine methanol solution 1mL, 500rpm. Fig.21It can be seen that within 100 mg, with the increase of catalyst dosage, the DMF yield gradually increased, proving that the catalytic reaction did not reach thermodynamic equilibrium.
[0134] The catalyst cycle stability experiment was conducted six times on the same catalyst. The reaction conditions were: 50mL intermittent high-pressure reactor, P = 6.0MPa, V (H2) / V (CO2) = 1 / 1, 100mg, T = 230℃, t = 12h, 1mL of 30wt% dimethylamine methanol solution, 500rpm; after each reaction, the reactor was cooled in an ice bath and the gaseous and liquid products were collected. The catalyst was washed with methanol and centrifuged 3 times after the reaction. After that, the catalyst was placed in a vacuum drying oven and vacuum dried at 80℃ for 2h. After taking it out, the catalyst was weighed and fresh catalyst was added to 0.1g, loaded into the reactor, the substrate was added, and the reaction gas was introduced to continue the next experiment. InZnAlO x (5%) The stability test results of the catalyst CO2, H2 and dimethylamine for synthesizing DMF are as follows Fig. 22 As shown. Fig. 22 It can be seen that with the increase in the number of cycles, the DMF yield did not change significantly and remained at around 40%, proving that the catalyst had good stability.
[0135] (ii) Catalytic performance (reaction of CO2, H2 and dimethylamine to produce DMF) test of the catalysts prepared in the examples and comparative examples using a slurry bed reactor (i.e., continuous flow method)
[0136] The activity of the catalyst for hydrogenation of CO2 to DMF was evaluated in a slurry bed reactor. The stainless steel reactor had a V = 3L. 6 g of catalyst was added to the system. A thermocouple probe was placed in the kettle to test the temperature inside the kettle. The system was heated to the required reaction temperature. H2 was introduced into the reactor at 10 mL / min through a mass flow meter, while dimethylamine methanol solution and liquid CO2 were introduced into the slurry bed reactor at 90 mL / h and 64 mL / h respectively through a liquid feed pump. The system pressure was adjusted using a back pressure valve to reach the expected reaction pressure. The liquid height in the kettle was controlled by a liquid back pressure valve, a liquid level gauge, and a pneumatic solenoid valve to ensure system stability. After a period of reaction, the product entered the product tank through cooling, and real-time sampling was performed at a certain time. The product was quantified by the gas phase, and the yield was calculated.
[0137] (1) Using a slurry bed reactor under low pressure conditions to synthesize InZnAlO x Preliminary evaluation of the catalyst's CO2 hydrogenation catalytic performance
[0138] The InZnAlO prepared in Example 1 was subjected to a slurry bed reactor at a certain temperature and a relatively low pressure. xThe catalytic performance of the (5%) catalyst for CO2 hydrogenation was preliminarily evaluated. The conditions of the catalytic test were: T = 200 °C, P = 4.5 MPa, V (H2) / V (CO2) = 1 / 1, GHSV = 500 mL (CO2 + H2) / (g cat h), dimethylamine methanol solution (30wt%) flow rate: 15mL / (g cat h), stirring: 100 rpm. Liquid NMR hydrogen spectrum was used to conduct offline qualitative analysis of the liquid product. The results are as follows Fig.23 As shown, in addition to the product DMF, there is trimethylamine (N(CH3)3), a by-product of DMF overhydrogenation.
[0139] DMF was prepared by hydrogenation of CO2 under the following conditions: T = 230 °C, P = 4.5 MPa, V(H2) / V(CO2) = 1 / 1, GHSV = 500 mL (CO2 + H2) / (g cat h), dimethylamine methanol solution (30wt%) flow rate: 15mL / (g cat h), stirring: 250 rpm. The gas products were separated and detected offline using a thermal conductivity detector (TCD). The test results are as follows: Fig.24 , and no CO byproduct appeared in the gas product. Using n-butanol as the internal standard solvent, a hydrogen flame ionization detector (FID) was used to separate and detect the liquid product offline for quantification. The results are as follows Fig.25 and Fig.26 The reaction yield of the reactor (4.5MPa reaction pressure, 5% DMF yield) is lower than that of the batch reactor (12MPa reaction pressure, 40.7% DMF yield), but after changing the feed amount, it was found that no by-product methyl dimethylcarbamate appeared, and the selectivity was improved to a certain extent, which may be due to the shorter residence time of the raw materials and the lower reaction pressure.
[0140] The above results show that the InZnAlOx (5%) catalyst still exhibits corresponding activity at a lower reaction pressure (4.5MPa).
[0141] (2) Optimize the stirring rate
[0142] Reaction conditions: T = 230 ° C, P = 7.0 MPa, V (H2) / V (CO2) = 1 / 1, GHSV = 750 mL (CO2 + H2) / (g cat h), dimethylamine methanol solution (30wt%) flow rate: 15mL / (g cat h), stirring rate: 100 rpm, 250 rpm, 400 rpm, reaction time 3 h, sampling again after 30 min interval. n-Butanol was used as internal standard solvent, and hydrogen flame ionization detector (FID) was used to separate and detect liquid products offline for quantification. The results are shown in Fig. 27 As shown. It can be seen that with the increase of stirring rate, the DMF yield gradually increases and reaches the upper limit at 250rpm. It is speculated that under the condition of low stirring speed, due to the influence of mass transfer, the external diffusion is insufficient and the product occupies the reaction site. After the speed is increased to 400rpm, the DMF yield drops to 13.3%. It is speculated that the speed may be too fast, causing the liquid and catalyst to splash, affecting the catalytic performance.
[0143] (3) Optimize the reaction temperature
[0144] Reaction conditions: T = 200 ~ 240 ° C, P = 7.0 MPa, V (H2) / V (CO2) = 1 / 1, GHSV = 1000 mL (CO2 + H2) / (g cat h), dimethylamine methanol solution (30wt%) flow rate: 15mL / (g cat h), stirring: 250 rpm. Fig.28 InZnAlO at different temperatures x (5%) The catalytic activity of the catalyst. It can be seen that the yield reaches a peak at 230°C, and the DMF yield reaches 14.3%, with a DMF selectivity close to 100%. When the temperature is further increased, the DMF yield gradually decreases. It is speculated that the CO2 hydrogenation to DMF reaction is an exothermic reaction. Further increasing the temperature will shift the equilibrium toward the reactants, inhibiting the reaction. With the change of temperature, the DMF selectivity changes little, fluctuating around 99%.
[0145] (4) Optimize the CO2 / H2 gas ratio
[0146] The effect of CO2 / H2 gas ratio on InZnAlO x The effect of (5%) catalyst on the activity of catalytic CO2 hydrogenation to DMF, the reaction conditions are: T = 230 ° C, P = 7.0 MPa, V (CO2) / V (H2) = 3 / 1, 2 / 1, 1 / 1, 1 / 2 or 1 / 3, GHSV = 1000 mL (CO2 + H2) / (g cat h), dimethylamine methanol solution (30wt%) flow rate: 15mL / (g cat h), stirring: 250 rpm. Fig.29 InZnAlO under different gas ratios x(5%) DMF yield graph of the catalyst. It can be seen that when the gas ratio is V(H2) / V(CO2)=1 / 1, the DMF yield is the highest, which is 14.3%. After that, the DMF selectivity decreases with the gradual increase of the H2 ratio. Through the chemical reaction equation: CO2+H2+NH(CH3)2→HCON(CH3)2+H2O, it can be seen that when CO2 and H2 reach a stoichiometric ratio of 1 / 1, they have the best activity, which is consistent with the experimental phenomenon of the intermittent reactor. It is inferred that because H2 and CO2 are continuously introduced into the system, the stable supply of gas raw materials is guaranteed, but the lower H2 ratio will result in insufficient H2 reaction of dimethylamine, and the conversion rate of dimethylamine will be reduced. On the other hand, a lower CO2 ratio will result in insufficient CO2 reaction of dimethylamine.
[0147] (5) Optimize airspeed
[0148] Space velocity is also one of the main reasons affecting catalytic activity. By changing the flow rate of reactant gas and liquid to adjust the space velocity of the system, the effect of space velocity on InZnAlO x (5%) The effect of catalyst on the activity of hydrogenation of CO2 to DMF, reaction conditions: T = 230 ° C, P = 7.0 MPa, V (H2) / V (CO2) = 1 / 1, GHSV = 500, 1000 or 2000 mL (CO2 + H2) / (g cat h), dimethylamine methanol solution (30wt%) flow rate: 7.5, 15 or 22.5mL / (g cat h), stirring: 250 rpm. Fig.30 InZnAlO at different space velocities x (5%) DMF yield of the catalyst. It can be seen that the product yield is dependent on the reaction residence time. As the space velocity gradually increases (500 to 2000mL (CO2 + H2) / (g cat h), the DMF yield dropped from 18.4% to 8.4% at a space velocity of 500 mL (CO2 + H2) / (g cat h) the DMF yield was the highest, reaching 18.4%, indicating that the conversion of dimethylamine takes a long time to complete. According to the evaluation of the catalyst reaction time of the intermittent reactor above, the reaction is beneficial under a longer time (12 h), which is consistent with the results obtained in the flow system.
[0149] (6) Optimize the ratio of liquid to gas raw materials
[0150] In order to determine the effect of the molar ratio between liquid and gas raw materials on the catalytic activity, the amount of dimethylamine feed was changed to explore the effect of the gas-liquid molar ratio on the catalytic activity of InZnAlO x(5%) Catalyst catalytic CO2 hydrogenation to DMF activity, reaction conditions: T = 230 ° C, P = 7.0 MPa, V (H2) / V (CO2) = 1 / 1, GHSV = 500 mL (CO2 + H2) / (g cat h), dimethylamine methanol solution (30wt%) flow rate: 3.75, 7.5, 15 or 22.5 mL / (g cat h), stirring: 250 rpm. Fig.31 InZnAlO with different liquid and gas raw material ratios x (5%) DMF yield of the catalyst. It can be seen that when the dimethylamine flow rate is large (22.5mL / (g cat h), 5 / 5 / 1) DMF yield was somewhat reduced (9.8%), while the dimethylamine flow rate gradually decreased to 7.5 mL / (g cat h) When the molar ratio is 20 / 20 / 1, InZnAlO x The activity of the catalyst for catalytic hydrogenation of CO2 to DMF reached (20.9%). With the further decrease of the flow rate, that is, when the molar ratio was 30 / 30 / 1, the InZnAlO x The activity of the catalyst for catalytic hydrogenation of CO2 to DMF reached saturation (21.4%). It is speculated that when the dimethylamine flow rate is high, dimethylamine does not fully participate in the reaction. When CO2 and H2 are greatly in excess, it is conducive to the efficient conversion of dimethylamine.
[0151] (7) Catalytic stability evaluation of the catalyst
[0152] Catalyst InZnAlO x (5%) was used to evaluate the catalytic stability for 100 h. The reaction conditions were: T = 230 °C, P = 7.0 MPa, V (H2) / V (CO2) = 1 / 1, GHSV = 500 mL (CO2 + H2) / (g cat h), dimethylamine methanol solution (30wt%) flow rate: 7.5mL / (g cat h), stirring: 250 rpm. Fig.32 InZnAlO x (5%) Catalyst stability evaluation results. It can be seen that the stability of the oxide catalyst is relatively good, and no significant decrease in DMF yield was observed within 100 hours. The DMF yield was low in the first 3 hours, and the catalyst may have an induction period (the fluctuation comes from the fact that the liquid level and pressure will be reduced to a certain extent when sampling).
[0153] It can be seen from the above examples that the non-precious metal heterogeneous catalyst provided by the present invention, i.e., Al-doped InZnAlO xThe catalyst exhibits excellent reactivity in the reaction of synthesizing DMF from CO2, H2 and dimethylamine, and has excellent stability.
[0154] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A non-precious metal heterogeneous catalyst, characterized in that: The invention comprises indium zinc bimetallic oxide and aluminum element doped in the indium zinc bimetallic oxide.
2. The non-precious metal heterogeneous catalyst according to claim 1, characterized in that The molar amount of indium in the non-precious metal heterogeneous catalyst is 30% to 60% of the total molar amount of indium and zinc, and the molar amount of aluminum is 2.5% to 10% of the total molar amount of indium, zinc and aluminum.
3. The non-precious metal heterogeneous catalyst according to claim 2, characterized in that: The molar amount of indium element in the non-noble metal heterogeneous catalyst is 45% of the total molar amount of indium element and zinc element.
4. The method for preparing the non-precious metal heterogeneous catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: Mixing indium salt, zinc salt, aluminum salt and water to obtain a metal salt mixed solution; The metal salt mixed solution and the soluble carbonate are mixed to perform a coprecipitation reaction to obtain a precipitate; The precipitate is calcined to obtain the non-precious metal heterogeneous catalyst.
5. The preparation method according to claim 4, characterized in that: The initial pH value of the coprecipitation reaction is 6-8.
6. The preparation method according to claim 4, characterized in that: The coprecipitation reaction comprises sequentially performing heating treatment and room temperature aging, wherein the temperature of the heating treatment is 60-80°C.
7. The preparation method according to claim 4, characterized in that: The calcination temperature is 450-550° C., the heat preservation time is 2-5 hours, and the calcination is carried out in an air atmosphere.
8. Use of the non-precious metal heterogeneous catalyst according to any one of claims 1 to 3 or the non-precious metal heterogeneous catalyst prepared by the preparation method according to any one of claims 4 to 7 in the reaction of carbon dioxide, hydrogen and dimethylamine to produce N,N-dimethylformamide.
9. The use according to claim 8, characterized in that: The reaction is carried out in a batch reactor, the charging pressure of the reaction is ≥3MPa, the temperature is 230°C, and the volume ratio of hydrogen to carbon dioxide is 1 / 1.
10. The use according to claim 8, characterized in that: The reaction is carried out in a slurry bed reactor at a temperature of 200 to 240° C., a reaction pressure of 7.0 MPa, a volume ratio of carbon dioxide to hydrogen of 3 / 1 to 1 / 3, and a GHSV of 500 to 2000 mL (CO2 + H2) / (g cat ·h), the flow rate of dimethylamine solution is 3.75~22.5mL / (g cat h), the mass fraction of the dimethylamine solution is 30wt%.
Citation Information
Cited By
Method for synthesizing DMF (Dimethyl Formamide) by electroreduction of carbon dioxide and dimethylamine
CN122446216A
A method for the electroreduction synthesis of dmf from carbon dioxide and dimethylamine
CN122446216B